Social Emotional Learning Program Boosts Early Social and Behavioral Skills in Low-Income Urban Children - Calhoun, Brian; Williams, Jason; Greenberg, Mark; Domitrovich, Celene; Russell, Michael A.; Fishbein, Diana H. (Frontiers in Psychology, 2020)
Social emotional learning (SEL) programs are increasingly being implemented in elementary schools to facilitate development of social competencies, decision making skills, empathy, and emotion regulation and, in effect, prevent poor outcomes such as school failure, conduct problems and eventual substance abuse. SEL programs are designed to foster these abilities in children with a wide range of behavioral, social and learning needs in the classroom, including children who are economically disadvantaged. In a previous study of kindergartners residing in a high poverty community, we observed significant behavioral improvements in children receiving an SEL program—The PATHS® curriculum (PATHS)--relative to an active control condition within one school year. The present investigation sought to determine whether these improvements were sustained over the course of two intervention years and an additional year when intervention was no longer provided. Further, we examined whether baseline measures of neurocognition and stress physiology—known to be adversely impacted by poverty and trauma—moderated heterogeneous outcomes. Finally, a preliminary analysis explored whether neurocognition and physiological stress reactivity (heart rate variability; HRV) predict change in outcomes post-intervention. Results confirmed that students who received PATHS sustained significant behavioral improvements over time. These effects occurred for the full sample, irrespective of putative baseline moderators, suggesting children in high risk environments may benefit from SEL interventions irrespective of baseline cognitive functioning as a function of overall substantial need. Of interest is that an examination focused specifically on change from waves 3 to 4 after the intervention concluded brought to light possible moderation by baseline physiology. We surmise that, when an intervention providing protective effects is withdrawn, children with higher HRV may not be able to regulate physiological stress responses to environmental challenges, leading to an uptick in maladaptive behaviors. In reverse, children with lower HRV—generally associated with poorer emotion regulation —may have incurred relatively greater gains in behavioral improvement due to lesser sensitivity to the environment, enabling them to continue to accrue benefits. Results are discussed in the context of possible pathways that may be relevant to understanding the special needs of children reared in very low income, high stress neighborhoods.